Safe operation and maintenance of dry dock facilities - Harren, Paul A., editor; Coasts, Oceans, Ports and Rivers Institute (American Society of Civil Engineers). Dry Dock Asset Management Task Committee (Reston, Va. : American Society of Civil Engineers)
Includes bibliographical references and index